Downregulation of serum exosomal miR‐320d predicts poor prognosis in hepatocellular carcinoma - Li, Wenxiao (J Clin Lab Anal, 2020)
BACKGROUND: MicroRNAs (miRNAs) is a class of functional regulator of tumorigenesis of human cancer including hepatocellular carcinoma (HCC). However, the potential clinical significance of serum exosomal miR‐320d in HCC has not been elucidated. METHODS: Real‐time reverse transcription PCR was used to detect the expression pattern of serum exosomal miR‐320d in patients with HCC, and the correlation between the deregulation of serum exosomal miR‐320d and the clinical outcome of HCC was explored. The biological function of exosomal miR‐320d in HCC was also investigated. RESULTS: Our results showed that the expression levels of exosomal miR‐320d were remarkably reduced in the serum samples of HCC patients and the culture medium of HCC cell lines compared with their respective controls. Serum exosomal miR‐320d could differentiate the HCC patients from healthy controls with high accuracy. In addition, its level was remarkably increased in the HCC patients who had received surgical treatment. Moreover, reduced serum exosomal miR‐320d was associated with advanced tumor stage, positive lymph node metastasis, and poorly differentiated tumors. HCC patients with lower serum exosomal miR‐320d had shorter overall and disease‐free survival. Low serum exosomal miR‐320d was identified to be an independent unfavorable prognostic factor for HCC. Finally, overexpression of miR‐320d inhibited the proliferation and invasion of HCC cells, and BMI1 was demonstrated to be a direct target of miR‐320d. CONCLUSION: Taken together, serum exosomal miR‐320d could be a potential non‐invasive biomarker for the diagnosis and prognosis of HCC.